Miniaturized 4 x 4 switched-beam butler matrix with bandwidth enhancement for 5G communication system - Mahyuddin, Nor Muzlifah; Mohd Suhaimi, Nazleen Syahira; Ismail, Widad; Mohd Ibrahim, Imran (Elsevier B.V., 2022)
A 4 x 4 Butler Matrix (BM) without phase shifter is proposed to provide bandwidth enhancement and size reduction by removing a conventional 0 dB/90⁰ crossover, two 0⁰ phase shifters and two 45 phase shifters. Two proposed 3 dB/45⁰ patch couplers replace the combination of two conventional 3 dB/90⁰ branch-line couplers and two 45⁰ phase shifters, whilst a modified0 dB/0⁰ crossover removes two 0⁰ phase shifters from the conventional BM. The -10 dB fractional bandwidths of reflection coefficients and isolations for the proposed BM are 18.46% in simulation and measurement. The -6 dB ± 1.5 dB average transmission coefficient and +45⁰, 135, +135⁰and +45⁰ of output phase differences with 1.8 average phase imbalance are accomplished at 6.5 GHz. The simulated and measured scattering parameters (S parameters) and phase differences are in close compliance with each other. Four switched-beams pointed at +15⁰, -50⁰, +50⁰ and +15⁰ are developed by integrating the proposed BM with inset feeding patch antennas. The proposed BM is miniaturized by 51.56%, whilst the bandwidth performance is enhanced by 9.7% compared to the conventional BM. Hence, this compact BM is a promising candidate for the fifth generation (5G) communication system.